Influence of technical challenges on construction project contracting - Coleman, Charles Egyabeng; Mwanaumo, Erastus Misheng’u; Muya, Mundia; Abdul Rahimi, Abdul Rahman (Penerbit Universiti Malaysia Pahang, 2025)
The construction industry plays a crucial role in economic development by providing essential infrastructure, creating jobs, and supporting other industries. However, this sector faces persistent technical challenges that impede successful project contracting, including issues, such as inadequate supervision, unskilled labour, and outdated equipment. Despite the industry's importance, there is limited research on how these technical challenges impact project contracting, creating a gap in understanding and addressing these issues effectively. This study investigates the influence of technical challenges on project contracting in construction. The data were gathered using a structured survey and Structural Equation Modelling (SEM) was used to analyse the impact of challenges like resource shortages, supply chain issues, and insufficient workforce skills on contracting outcomes. The findings revealed lack of qualified supervision, unskilled labour resulting in poor workmanship, material shortages due to defective supply chains, and ambiguous project specifications as significant challenges that influence projects. The structural equation modelling confirms the reliability of the proposed model, highlighting the interplay between identified technical challenges and their latent constructs. These findings highlight the need to invest in training programs in ensuring that project supervisors and managers possess the necessary qualifications and skills to effectively oversee construction projects. The study concludes by outlining suggestions for further research to deepen the understanding of technical challenges in the delivery of construction contracts and inform evidence-based strategies for industry improvement. This research not only addresses gaps in current literature but also provides practical recommendations for optimising contract deliverables in the construction industry.